Biological and computational evaluation of resveratrol inhibitors against Alzheimer's disease. (2nd January 2016) - Koukoulitsa, Catherine; Villalonga-Barber, Caroline; Csonka, Robert; Alexi, Xanthippi; Leonis, Georgios; Dellis, Dimitris; Hamelink, Elizabeth; Belda, Oscar; Steele, Barry R.; Micha-Screttas, Maria; Alexis, Michael N.; Papadopoulos, Manthos G.; et al.
Abstract: It has been reported that beta amyloid induces production of radical oxygen species and oxidative stress in neuronal cells, which in turn upregulates β-secretase (BACE-1) expression and beta amyloid levels, thereby propagating oxidative stress and increasing neuronal injury. A series of resveratrol derivatives, known to be inhibitors of oxidative stress-induced neuronal cell death (oxytosis) were biologically evaluated against BACE-1 using homogeneous time-resolved fluorescence (TRF) assay. Correlation between oxytosis inhibitory and BACE-1 inhibitory activity of resveratrol derivatives was statistically significant, supporting the notion that BACE-1 may act as pivotal mediator of neuronal cell oxytosis. Four of the biologically evaluated resveratrol analogs demonstrated considerably higher activity than resveratrol in either assay. The discovery of some "hits" led us to initiate detailed docking studies associated with Molecular Dynamics in order to provide a plausible explanation for the experimental results and understand their molecular basis of action.